2020
DOI: 10.1177/0265532220912412
|View full text |Cite
|
Sign up to set email alerts
|

Placement testing: One test, two tests, three tests? How many tests are sufficient?

Abstract: Accurate placement within levels of an ESL program is crucial for optimal teaching and learning. Commercially available tests are commonly used for placement, but their effectiveness has been found to vary. This study uses data from the Ohio Program of Intensive English (OPIE) at Ohio University to examine the value of two commercially available tests (the TOEFL ITP and the Michigan EPT) and a locally developed writing test for accurate placement decisions. Placement accuracy was measured in terms of the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…One of the critical criteria for a placement test is, thus, to include test tasks which “enable valid inferences regarding mastery of knowledge, abilities or skills taught on the course” (Green & Weir, 2004 , p. 469) so as to counter the two threats to construct validity known as “construct under-representation” and “construct-irrelevant variance ” (Messick, 1996 , p. 244). In this regard, to what extent the test task characteristics, including text and task features, align with the content of instruction emerges as an important indicator of the effectiveness of placement decisions (Hille & Cho, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the critical criteria for a placement test is, thus, to include test tasks which “enable valid inferences regarding mastery of knowledge, abilities or skills taught on the course” (Green & Weir, 2004 , p. 469) so as to counter the two threats to construct validity known as “construct under-representation” and “construct-irrelevant variance ” (Messick, 1996 , p. 244). In this regard, to what extent the test task characteristics, including text and task features, align with the content of instruction emerges as an important indicator of the effectiveness of placement decisions (Hille & Cho, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conflicting results in previous studies have attracted increasing research attention. Hille and Cho ( 2020 ) recently examined placement accuracy by comparing ESL students’ test scores on two commercially available tests and one locally developed writing test with their actual placement levels determined by their teachers. The results revealed that each test by itself performed similarly in predicting student placement and the combined use of all three tests produced the highest accuracy, yet neither individual tests nor any combinations of these tests could significantly predict students’ course grades and advancement to the next level.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations